2022 RIVF International Conference on Computing and Communication Technologies (RIVF) 2022
DOI: 10.1109/rivf55975.2022.10013883
|View full text |Cite
|
Sign up to set email alerts
|

Multi Kernel Positional Embedding ConvNeXt for Polyp Segmentation

Abstract: Medical image segmentation is the technique that helps doctor view and has a precise diagnosis, particularly in Colorectal Cancer. Specifically, with the increase in cases, the diagnosis and identification need to be faster and more accurate for many patients; in endoscopic images, the segmentation task has been vital to helping the doctor identify the position of the polyps or the ache in the system correctly. As a result, many efforts have been made to apply deep learning to automate polyp segmentation, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Nguyen et al suggested a method for polyps segmentation that integrates the Multi Kernel Positional Embedding block (MPE) with the ConvNeXt backbone to extend the receptive field and obtain multi-scale information [14]. This method achieved a dice coefficient of 0.88 on the Kvasir-SEG dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Nguyen et al suggested a method for polyps segmentation that integrates the Multi Kernel Positional Embedding block (MPE) with the ConvNeXt backbone to extend the receptive field and obtain multi-scale information [14]. This method achieved a dice coefficient of 0.88 on the Kvasir-SEG dataset.…”
Section: Related Workmentioning
confidence: 99%